Perceived Educational Needs of Postmenopausal Iranian Women: A Qualitative Study - Foozieh Rafati; Najme Pourshahrokhi; Neda Dastyar (Kerman University of Medical Sciences, 2022)
Background: Menopause is a natural change that almost all women experience in middle age. Just like puberty, menopause is considered a turning point in a woman's life. Postmenopausal women experience a wide range of symptoms that may affect their health and well-being, but in most cases, they are unaware of the postmenopausal symptoms they are experiencing or will experience. This study aimed to investigate the perceived educational needs of postmenopausal women in southern Iran. Methods: This study was conducted using a conventional qualitative content analysis approach in 2021 in Jiroft (southern Iran). The main research question was, 'What educational needs do postmenopausal women experience?' To answer this question, 15 participants were selected using purposive sampling (seven postmenopausal women, four gynecologists, three midwifery experts, and one nutritionist). The data were collected using semi-structured interviews, which continued until data saturation. The collected data were analyzed using the method proposed by Graneheim and Lundman. The MAXQDA 12 software was used to manage qualitative data analysis. Results: Data analysis revealed one main theme (perceived educational needs) with two categories and five subcategories: (a) Perceived information and medical needs (the need to know about the healthy transition to menopause, the need for support and advice in health-related decisions, and health-promoting educational needs) and (b) The need for self-control (the need for self-management of physical symptoms and the need for self-management of psychological symptoms). Conclusion: This study showed that postmenopausal women face many physical and psychological challenges and need more education to better meet these challenges. Thus, officials and experts in charge of women's health such as gynecologists, midwives, nurses, and care providers need to pay special attention to problems and issues of postmenopausal women and plan to promote their awareness and knowledge.